Patient satisfaction in basic dental care clinic - Rosell, Fernanda Lopez [UNESP]; Valsecki Junior, Aylton [UNESP]; Genaro, Luís Eduardo [UNESP]; Pinotti, Felipe Eduardo [UNESP] (Faculdade São Leopoldo Mandic, 2024)
The interaction between dental students and patients is essential for practical and realistic learning, providing community services, and establishing a dental school clinic. Simultaneously, studies on public healthcare user satisfaction are crucial, contributing to corrective measures planning based on obtained information. The study aimed to understand the demographic and economic profile of patients treated at the Basic Dental Care Clinic of a public university and to assess patient satisfaction with the services and infrastructure. A cross-sectional observational study was conducted, collecting socioeconomic and general health data from patients through dental anamnesis. Validated questionnaires were used: Questionnaire for User Satisfaction with Public Oral Health Services, covering seven quality dimensions, and the Pompeu Questionnaire, addressing dental care aspects. Responses were tabulated for descriptive statistical analysis. Results: Questionnaire for User Satisfaction with Public Oral Health Services results indicate high patient satisfaction in various dimensions, such as human relations, treatment effectiveness, accessibility, and technical-scientific quality. The Pompeu Questionnaire reinforces these findings, emphasizing the students’ and professors’ receptiveness, effective guidance on oral care, and a high clinic recommendation rate by patients. In summary, both questionnaires reveal an overall positive patient satisfaction. In the study’s context, the majority of patients treated in the mentioned clinic expressed satisfaction with the physical structure, service, and dental treatment offered.

A interação entre alunos de odontologia e pacientes é essencial para um aprendizado prático e próximo da realidade, oferecendo serviços à comunidade e configurando uma clínica-escola. Paralelamente, estudos sobre a satisfação do usuário do sistema público de saúde são fundamentais, contribuindo para o planejamento de medidas corretivas com base nas informações obtidas. O estudo teve os objetivos de conhecer o perfil demográfico e econômico dos pacientes atendidos na Clínica de Atenção Básica Odontológica de uma Faculdade pública; e avaliar a satisfação dos pacientes em relação ao serviço prestado e a infraestrutura da Clínica. Realizou-se um estudo transversal observacional, coletando dados socioeconômicos e de saúde geral de pacientes por meio de anamneses odontológicas. Utilizaram-se questionários validados: Questionário de Satisfação dos Usuários com os Serviços Públicos de Saúde Bucal, que abrange sete dimensões de qualidade, e o Questionário Pompeu, que contém aspectos do atendimento odontológico. As respostas foram tabuladas para análise estatística descritiva. Resultados: Os resultados do Questionário de Satisfação dos Usuários com os Serviços Públicos de Saúde Bucal indicam elevada satisfação dos pacientes em diversas dimensões, como relações humanas, eficácia do tratamento, acessibilidade e qualidade técnico-científica. O Questionário de Pompeu reforça esses achados, destacando a receptividade dos alunos e professores, orientações eficazes sobre cuidados bucais e uma alta taxa de recomendação da clínica pelos pacientes. Em resumo, ambos os questionários revelam uma satisfação geral positiva dos pacientes. Diante do cenário no momento do estudo, a grande maioria dos pacientes atendidos na referida clínica, sentem-se satisfeitos com a estrutura física, de atendimento e tratamento odontológico oferecidos.
Satisfação dos pacientes atendidos em Clínica de Atenção Básica Odontológica
Keywords: Dentistry; Patient satisfaction; Unified Health System; Satisfação do paciente; Odontologia; Sistema Único de Saúde